Does escaping victimization in elementary school lead to improved health in high school: a comparison of victimization profile groups. Issue 4 (22nd May 2017) - Jensen‐Campbell, Lauri A.; Boyd, Erin Q.; Arana, Allyson A.; Lee, Sarah
Abstract : This study examined whether children follow unique victimization trajectories during elementary school and whether these paths predict differential psychological and physical health outcomes during high school. Participants included 1, 073 children from the NICHD Study of Early Child Care and Youth Development. Peer victimization was assessed in the 3rd, 5th, 6th, and 9th grades, and psychological and physical health outcomes (e.g., depression, loneliness, internalizing problems, externalizing problems, physical health markers, and health habits) were measured in the 9th grade. Growth mixture modeling revealed three groups: non‐victims ( n = 886), persistent victims ( n = 52), and escaped victims ( n = 70). Generally, persistent victims experienced poorer physical functioning and health, higher levels of psychological maladjustments, and poorer health habits (i.e., sleep problems, disordered eating) compared to non‐victims. Using case–control matching, escaped victims and non‐victims did not differ on health behaviors and most physical health measures, with the exception of adiposity. Escaped victims experienced higher levels of psychological issues than non‐victims comparable to those observed in persistent victims. These findings underscore the heterogeneity of both victimization experiences and health outcomes following aversive peer experiences.